Beyond desertification: new paradigms for dryland landscapes. Issue 1 (1st February 2015) - Peters, Debra PC; Havstad, Kris M; Archer, Steven R; Sala, Osvaldo E
Abstract : The traditional desertification paradigm focuses on the losses of ecosystem services that typically occur when grasslands transition to systems dominated by bare (unvegetated) ground or by woody plants that are unpalatable to domestic livestock. However, recent studies reveal complex transitions across a range of environmental conditions and socioeconomic contexts. The papers in this Special Issue illustrate how an improved understanding of these dynamics is generating more robust paradigms, where state changes and regime shifts occurring within the context of changes in land use and climate are modified by landform and antecedent conditions. New and emerging technologies are being used to characterize and evaluate processes and outcomes across various scales and levels of organization. At the same time, developments in education are taking advantage of these new perspectives to improve the ecological literacy of future generations, and to better inform land‐management decisions. A framework that integrates these perspectives provides a more comprehensive approach for understanding and predicting dryland dynamics.